BUDAYA KONSUMTIF MAHASISWA DI ERA DIGITAL ANTARA GAYA HIDUP DAN TEKANAN SOSIAL - Rizqi Nurul Azizah (Yayasan Literasi Sains Indonesia, 2026)
Consumptive culture among university students has increasingly developed alongside rapid digital technological advancement and the widespread use of social media in daily life. Consumption is no longer carried out merely to fulfill basic needs, but has become a means of constructing self-identity, displaying social status, and gaining recognition within digital spaces. This article aims to analyze this phenomenon from a sociological perspective by applying Jean Baudrillard’s theory of simulacra, which explains how social reality is shaped by symbols, images, and representations that are continuously reproduced.The method used in this study is a literature review, examining various scientific journals and relevant sources related to consumption, culture, identity, and social pressure. The findings indicate that students’ consumptive behavior is influenced by digital social structures that create indirect social pressure through online interactions. Ideal lifestyle standards are massively displayed and reproduced, encouraging students to constantly adjust themselves in order to maintain social existence and relevance. Consumptive culture has both positive and negative impacts. On one hand, consumption can serve as a form of self-expression and creativity. On the other hand, it may negatively affect students’ financial stability, mental health, and academic focus. Therefore, a critical understanding is necessary so that students can manage their consumption patterns rationally and wisely amid the ongoing development of digital culture.